X-ray shielding material and production process thereof
By using specific combined materials and processes, X-ray shielding materials with high shielding performance and excellent mechanical properties are prepared, which solves the problem of the reduction in flexibility of traditional materials at high metal content and achieves a more effective X-ray shielding effect.
Patent Information
- Application Number
- CN202210376045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-04-11
AI Technical Summary
When the metal content of traditional X-ray shielding materials reaches more than 86 wt%, the plasticity and softness of the flexible material will be greatly reduced, which will easily break or surface cracks, resulting in a decrease in effective use thickness and a decrease in ray shielding ability.
A combined material including 86-95% shielding powder, 4.7-13.8% liquid silicone, 0.1-5% nano silicon carbide whiskers, 0.05-4% nano carbon tubes and 0.05-0.1% curing agent was prepared by casting method and infrared and ultraviolet radiation.
It achieves the improvement of the strength, toughness and flexural strength of the material while ensuring high shielding elements, and improves the comprehensive mechanical properties and effective shielding ability of the X-ray shielding material.
Smart Images

Figure BDA0003590426790000091 
Figure BDA0003590426790000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of radiation protection, and in particular, relates to an X-ray shielding material and a production process thereof. Background Art
[0002] X-rays are a type of electromagnetic wave with a short wavelength and strong penetrating power, and are widely used in medical and other fields. Long-term exposure to X-rays can cause great harm to the human body, and exceeding a certain dose can also cause leukemia, tumors and other diseases. Generally, elements with higher atomic numbers and higher densities are used as protective shielding materials.
[0003] The traditional protection scheme is to use lead to make lead plates, lead glass, etc. as protective materials. Since lead is a toxic element, it is gradually replaced by tungsten, molybdenum, nickel and other elements, and these metal materials are combined with rubber to make flexible materials. However, when the metal content in such products reaches more than 86wt%, the plasticity and softness of the flexible material will be greatly reduced, and it will be easy to break or have surface cracks. After cracks occur, the effective use thickness of the material is reduced. If a through crack occurs, the radiation shielding ability at the crack is close to zero. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide an X-ray shielding material and a production process thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An X-ray shielding material comprises, by weight percentage, 86-95% of shielding powder material, 4.7-13.8% of liquid silica gel, 0.1-5% of nano silicon carbide whisker, 0.05-4% of nano carbon tube and 0.05-0.1% of curing agent.
[0007] Furthermore, the shielding powder material includes tungsten powder, molybdenum powder, titanium powder and rhenium powder, and the mass ratio of the powder is 1:0.47-0.52:0.1-0.2:0.2-0.3 respectively.
[0008] Preferably, the tungsten powder is spherical particles with a Fischer-Tropsch particle size of 10-20 μm, the molybdenum powder has a Fischer-Tropsch particle size of 3-4 μm, the titanium powder has a Fischer-Tropsch particle size of 1-3 μm, and the rhenium powder has a Fischer-Tropsch particle size of 3-5 μm.
[0009] Preferably, the diameter of the nano-silicon carbide whisker is 3-60 nm and the length is 20-500 nm.
[0010] Preferably, the carbon nanotube has a diameter of 2-100 nm and a length of 200-6000 nm.
[0011] Preferably, the liquid silicone is methyl vinyl silicone with a viscosity of 5000 cPs.
[0012] A production process of an X-ray shielding material comprises the following steps:
[0013] Step S1: evaporating the nano-silicon carbide whiskers and nano-carbon tubes after coupling treatment to reduce the agglomeration of the nano-materials and improve the dispersibility of the nano-materials;
[0014] Step S2: adding tungsten powder, molybdenum powder, titanium powder, rhenium powder, nano-silicon carbide whiskers and carbon nanotubes treated in step S1 into a powder mixer and dry mixing for 72 hours to fully mix the powders to obtain a composite powder material;
[0015] Step S3: adding liquid silicone to a stirring kettle, adding composite powder material and mixing evenly, then adding curing agent and continuing to mix, so that the liquid silicone is initially cured to obtain a composite adhesive material;
[0016] Step S4: adding the composite adhesive material into a casting machine and extruding it into a casting film, and introducing hot air at 40° C. to dry the casting film so that the surface of the casting film is solidified but the core remains soft, thereby obtaining a semi-solidified film;
[0017] Step S5: sequentially subjecting the semi-solidified film to infrared irradiation, rolling and ultraviolet irradiation to obtain an X-ray shielding material.
[0018] Furthermore, the specific method of the coupling treatment is: ultrasonically disperse the nano-silicon carbide whiskers and the nano-carbon tubes in an ethanol solution, add KH550 and ultrasonically disperse them again, and then soak them for 24 hours.
[0019] Furthermore, the infrared wavelength of the infrared irradiation is 5-30 μm, the irradiation power is 220-300 W, the irradiation distance is 10-15 cm, and the irradiation time is 25-40 min.
[0020] Furthermore, the rolling pressure is 6-10 kN.
[0021] Furthermore, the ultraviolet wavelength of the ultraviolet irradiation is 100-200nm, the irradiation power is 150-200W, the irradiation distance is 10-20cm, and the irradiation time is 20-30min.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention uses large-sized spherical tungsten powder compounded with fine-sized molybdenum powder, titanium powder and rhenium powder as shielding raw materials to increase the volume ratio in liquid silica gel. The content of shielding elements in the finished product reaches more than 86%, and the density reaches 5.625g / cm 3 -10.387g / cm 3 , has excellent X-ray shielding effect.
[0024] 2. The present invention uses a certain ratio of nano-silicon carbide whiskers and nano-carbon tubes in the raw materials. The carbon nano-tubes are in a tubular structure with a hollow mesh surface, and the nano-silicon carbide whiskers are in a thin and short fiber structure. The nano-silicon carbide whiskers are interspersed between the nano-carbon tubes and the silica gel matrix to form a pinning effect, thereby simultaneously improving the strength, toughness and flexural strength of the material.
[0025] 3. The present invention provides a forming method of a shielding material, which first uses a casting method to cast a composite adhesive material into a film. During the casting process, hot air drying is used to initially solidify the surface of the film, keeping the interior in a soft colloidal state. After that, infrared irradiation is used to promote the migration and diffusion rate of metal elements, accelerate the migration of voids within the same time, and improve the volume ratio. Thanks to the solidification state of the surface layer of the film, a rolling process can be used after infrared irradiation to increase the density of the material. The improvement of the volume ratio and density improves the ability to resist radiation and shield rays. Finally, ultraviolet irradiation is used to artificially age the rolled film, so that the material achieves good comprehensive mechanical properties. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] This embodiment prepares an X-ray shielding material, and the specific implementation process is as follows:
[0029] Step 1: Take 86 kg of tungsten powder, molybdenum powder, titanium powder and rhenium powder in a mass ratio of 1:0.47:0.2:0.3 for standby use, wherein the tungsten powder is commercially available tungsten powder after spheroidization treatment, the tungsten powder particles are spherical, the calibrated Fischer particle size of the tungsten powder is 10 μm, the Fischer particle size of the molybdenum powder is 3-4 μm, the Fischer particle size of the titanium powder is 1-3 μm, and the Fischer particle size of the rhenium powder is 3-5 μm; then take 13.8 kg of methyl vinyl silica gel for standby use, take dibutyltin dilaurate and ethyl orthosilicate and mix them in a mass ratio of 1:1 as a curing agent, and take 50 g of the curing agent for standby use;
[0030] Step 2: 100g of nano-silicon carbide whiskers and 50g of nano-carbon tubes, wherein the nano-silicon carbide whiskers have a nominal diameter of 3nm and a nominal length of 20nm, and the nano-carbon tubes have a nominal diameter of 2nm and a nominal length of 200nm, the nano-silicon carbide whiskers and nano-carbon tubes are placed in 400mL of 50% ethanol aqueous solution by mass fraction, ultrasonically dispersed at 28kHz for 20min, allowed to stand for 1h, and then 50mL of KH550 is added, and ultrasonic dispersion is continued for 10min, and then the dispersion is first centrifuged and concentrated, and the precipitate is rotary evaporated to constant weight to obtain pretreated nano-silicon carbide whiskers and nano-carbon tubes;
[0031] Step 3: Add tungsten powder, molybdenum powder, titanium powder, rhenium powder and the treated nano silicon carbide whiskers and nano carbon tubes into a powder mixer and dry mix for 72 hours to fully mix the powders to obtain a composite powder material;
[0032] Step 4: Add liquid silicone (methyl vinyl silicone, viscosity of 5000 cPs) into the stirring tank, control the stirring rate to 60 rpm, uniformly add the composite powder, pretreated nano silicon carbide whiskers and nano carbon tubes into the stirring tank, stir for 30 minutes, mix the raw materials evenly, then add the curing agent into the stirring tank, continue stirring and mixing for 10 minutes to obtain a composite adhesive;
[0033] Step 5: Set the gap between the rollers of the casting machine to 2.2 mm, add the composite adhesive into the casting machine, extrude the composite adhesive from the gap between the rollers into a casting film, blow hot air at 40°C during the conveying of the casting film, and control the blowing time to be 1 hour, so that the surface of the casting film is solidified but the core remains soft, and a semi-solidified film is obtained;
[0034] Step 6: The semi-solidified film is irradiated with infrared light for 40 minutes, the irradiation source is 10 cm away from the semi-solidified film, the infrared wavelength of the infrared irradiation is 5-30 μm, and the irradiation power is 220 W;
[0035] Step 7: Put the infrared irradiated film into a roller mill, with a roller diameter of 110 mm, a roller speed of 280 rpm, a roller center diameter convexity of 0.03 mm, a rolling pressure of 6 kN, and roll it into a film with a thickness of 1.4 mm;
[0036] Step 8: The rolled film is subjected to ultraviolet irradiation for 30 minutes, the irradiation source is 10 cm away from the semi-solidified film, the ultraviolet wavelength of the ultraviolet irradiation is 5-30 μm, and the irradiation power is 150 W, to obtain an X-ray shielding material;
[0037] Step 9: Apply adhesive to the X-ray shielding material, paste the fabric, and cut it to make a prefabricated product.
[0038] Example 2
[0039] This embodiment prepares an X-ray shielding material, and the specific implementation process is as follows:
[0040] Step 1: Take 86 kg of tungsten powder, molybdenum powder, titanium powder and rhenium powder in a mass ratio of 1:0.52:0.1:0.2 for standby use, wherein the tungsten powder is commercially available tungsten powder after spheroidization treatment, the tungsten powder particles are spherical, the calibrated Fischer particle size of the tungsten powder is 20 μm, the Fischer particle size of the molybdenum powder is 3-4 μm, the Fischer particle size of the titanium powder is 1-3 μm, and the Fischer particle size of the rhenium powder is 3-5 μm; then take 4.9 kg of methyl vinyl silica gel for standby use, take dibutyltin dilaurate and ethyl orthosilicate and mix them in a mass ratio of 1:1 as a curing agent, and take 100 g of the curing agent for standby use;
[0041] Step 2: 5 kg of nano-silicon carbide whiskers and 4 kg of nano-carbon tubes, wherein the nano-silicon carbide whiskers have a nominal diameter of 50 nm and a nominal length of 500 nm, and the nano-carbon tubes have a nominal diameter of 60 nm and a nominal length of 6000 nm, the nano-silicon carbide whiskers and nano-carbon tubes are placed in 8 L of 50% ethanol aqueous solution by mass, ultrasonically dispersed at 28 kHz for 40 min, allowed to stand for 1 h, and then 500 mL of KH550 is added, and ultrasonic dispersion is continued for 20 min, and then the dispersion is first centrifuged and concentrated, and the precipitate is rotary evaporated to constant weight to obtain pretreated nano-silicon carbide whiskers and nano-carbon tubes;
[0042] Step 3: Add tungsten powder, molybdenum powder, titanium powder, rhenium powder and the treated nano silicon carbide whiskers and nano carbon tubes into a powder mixer and dry mix for 72 hours to fully mix the powders to obtain a composite powder material;
[0043] Step 4: Add liquid silicone (methyl vinyl silicone, viscosity 5000 cPs) into the stirring tank, control the stirring rate to 60 rpm, uniformly add the composite powder, pretreated nano silicon carbide whiskers and nano carbon tubes into the stirring tank, stir for 50 minutes, mix the raw materials evenly, then add the curing agent into the stirring tank, continue stirring and mixing for 10 minutes to obtain a composite adhesive;
[0044] Step 5: Set the gap between the rollers of the casting machine to 2.2 mm, add the composite adhesive into the casting machine, extrude the composite adhesive from the gap between the rollers into a casting film, blow hot air at 40°C during the conveying of the casting film, and control the blowing time to be 1 hour, so that the surface of the casting film is solidified but the core remains soft, and a semi-solidified film is obtained;
[0045] Step 6: The semi-solidified film is irradiated with infrared light for 30 minutes, the irradiation source is 15 cm away from the semi-solidified film, the infrared wavelength of the infrared irradiation is 5-30 μm, and the irradiation power is 300 W;
[0046] Step 7: Put the infrared irradiated film into a roller mill, with a roller diameter of 110 mm, a roller speed of 280 rpm, a roller center diameter convexity of 0.03 mm, a rolling pressure of 10 kN, and roll it into a film with a thickness of 1.4 mm;
[0047] Step 8: The rolled film is subjected to ultraviolet irradiation for 30 minutes, the irradiation source is 20 cm away from the semi-solidified film, the ultraviolet wavelength of the ultraviolet irradiation is 5-30 μm, and the irradiation power is 200 W, to obtain an X-ray shielding material;
[0048] Step 9: Apply adhesive to the X-ray shielding material, paste the fabric, and cut it to make a prefabricated product.
[0049] Example 3
[0050] This embodiment prepares an X-ray shielding material, and the specific implementation process is as follows:
[0051] Step 1: Take 95 kg of tungsten powder, molybdenum powder, titanium powder and rhenium powder in a mass ratio of 1:0.5:0.15:0.25 for standby, wherein the tungsten powder is commercially available tungsten powder after spheroidization treatment, the tungsten powder particles are spherical, the calibrated Fischer particle size of tungsten powder is 20 μm, the Fischer particle size of molybdenum powder is 3-4 μm, the Fischer particle size of titanium powder is 1-3 μm, and the Fischer particle size of rhenium powder is 3-5 μm; then take 4.7 kg of methyl vinyl silica gel for standby, take dibutyltin dilaurate and ethyl orthosilicate and mix them in a mass ratio of 2:3 as a curing agent, and take 100 g of the curing agent for standby;
[0052] Step 2: 100 g of nano-silicon carbide whiskers and 100 g of nano-carbon tubes, wherein the nano-silicon carbide whiskers have a nominal diameter of 3 nm and a nominal length of 500 nm, and the nano-carbon tubes have a nominal diameter of 100 nm and a nominal length of 6000 nm, the nano-silicon carbide whiskers and nano-carbon tubes are placed in 450 mL of a 50% ethanol aqueous solution by mass fraction, ultrasonically dispersed at 28 kHz for 40 min, allowed to stand for 1 h, and then 50 mL of KH550 was added, and ultrasonic dispersion was continued for 10 min, and then the dispersion was first centrifuged and concentrated, and the precipitate was rotary evaporated to constant weight to obtain pretreated nano-silicon carbide whiskers and nano-carbon tubes;
[0053] Step 3: Add tungsten powder, molybdenum powder, titanium powder, rhenium powder and the treated nano silicon carbide whiskers and nano carbon tubes into a powder mixer and dry mix for 72 hours to fully mix the powders to obtain a composite powder material;
[0054] Step 4: Add liquid silicone (methyl vinyl silicone, viscosity of 5000 cPs) into the stirring tank, control the stirring rate to 60 rpm, uniformly add the composite powder, pretreated nano silicon carbide whiskers and nano carbon tubes into the stirring tank, stir for 30 minutes, mix the raw materials evenly, then add the curing agent into the stirring tank, continue stirring and mixing for 10 minutes to obtain a composite adhesive;
[0055] Step 5: Set the gap between the rollers of the casting machine to 2.2 mm, add the composite adhesive into the casting machine, extrude the composite adhesive from the gap between the rollers into a casting film, blow hot air at 40°C during the conveying of the casting film, and control the blowing time to be 1 hour, so that the surface of the casting film is solidified but the core remains soft, and a semi-solidified film is obtained;
[0056] Step 6: The semi-solidified film is irradiated with infrared light for 30 minutes, the irradiation source is 15 cm away from the semi-solidified film, the infrared wavelength of the infrared irradiation is 5-30 μm, and the irradiation power is 300 W;
[0057] Step 7: Put the infrared irradiated film into a roller mill, with a roller diameter of 110 mm, a roller speed of 280 rpm, a roller center diameter convexity of 0.03 mm, a rolling pressure of 10 kN, and roll it into a film with a thickness of 1.4 mm;
[0058] Step 8: The rolled film is subjected to ultraviolet irradiation for 30 minutes, the irradiation source is 20 cm away from the semi-solidified film, the ultraviolet wavelength of the ultraviolet irradiation is 5-30 μm, and the irradiation power is 200 W, to obtain an X-ray shielding material;
[0059] Step 9: Apply adhesive to the X-ray shielding material, paste the fabric, and cut it to make a prefabricated product.
[0060] Example 4
[0061] This embodiment prepares an X-ray shielding material, and the specific implementation process is as follows:
[0062] Step 1: Take 91.8 kg of tungsten powder, molybdenum powder, titanium powder and rhenium powder in a mass ratio of 1:0.5:0.15:0.25 for standby, wherein the tungsten powder is commercially available tungsten powder after spheroidization treatment, the tungsten powder particles are spherical, the calibrated Fischer particle size of tungsten powder is 20 μm, the Fischer particle size of molybdenum powder is 3-4 μm, the Fischer particle size of titanium powder is 1-3 μm, and the Fischer particle size of rhenium powder is 3-5 μm; then take 6.4 kg of methyl vinyl silica gel for standby, take dibutyltin dilaurate and ethyl orthosilicate and mix them in a mass ratio of 2:3 as a curing agent, and take 100 g of the curing agent for standby;
[0063] Step 2: 700g of nano-silicon carbide whiskers and 1kg of nano-carbon tubes, wherein the nano-silicon carbide whiskers have a nominal diameter of 10nm and a nominal length of 300nm, and the nano-carbon tubes have a nominal diameter of 100nm and a nominal length of 1500nm, the nano-silicon carbide whiskers and nano-carbon tubes are placed in 5L of 50% ethanol aqueous solution by mass, ultrasonically dispersed at 28kHz for 50min, allowed to stand for 1h, and then 250mL of KH550 is added, and ultrasonic dispersion is continued for 10min, and then the dispersion is first centrifuged and concentrated, and the precipitate is rotary evaporated to constant weight to obtain pretreated nano-silicon carbide whiskers and nano-carbon tubes;
[0064] Step 3: Add tungsten powder, molybdenum powder, titanium powder, rhenium powder and the treated nano silicon carbide whiskers and nano carbon tubes into a powder mixer and dry mix for 72 hours to fully mix the powders to obtain a composite powder material;
[0065] Step 4: Add liquid silicone (methyl vinyl silicone, viscosity of 5000 cPs) into the stirring tank, control the stirring rate to 60 rpm, uniformly add the composite powder, pretreated nano silicon carbide whiskers and nano carbon tubes into the stirring tank, stir for 30 minutes, mix the raw materials evenly, then add the curing agent into the stirring tank, continue stirring and mixing for 10 minutes to obtain a composite adhesive;
[0066] Step 5: Set the gap between the rollers of the casting machine to 2.2 mm, add the composite adhesive into the casting machine, extrude the composite adhesive from the gap between the rollers into a casting film, blow hot air at 40°C during the conveying of the casting film, and control the blowing time to be 1 hour, so that the surface of the casting film is solidified but the core remains soft, and a semi-solidified film is obtained;
[0067] Step 6: The semi-solidified film is irradiated with infrared for 30 minutes, the irradiation source is 10 cm away from the semi-solidified film, the infrared wavelength of the infrared irradiation is 5-30 μm, and the irradiation power is 300 W;
[0068] Step 7: Put the infrared irradiated film into a roller mill, with a roller diameter of 110 mm, a roller speed of 280 rpm, a roller center diameter convexity of 0.03 mm, and a rolling pressure of 8 kN, and roll the film into a film with a thickness of 1.4 mm;
[0069] Step 8: The rolled film is irradiated with ultraviolet light for 20 minutes, the irradiation source is 10 cm away from the semi-solidified film, the ultraviolet wavelength of the ultraviolet light is 5-30 μm, and the irradiation power is 200 W, to obtain an X-ray shielding material;
[0070] Step 9: Apply adhesive to the X-ray shielding material, paste the fabric, and cut it to make a prefabricated product.
[0071] Samples (thickness 1.4 mm) of the X-ray shielding materials prepared in Examples 1 to 4 were taken, and X-rays were generated using a standard X-ray machine (model MG-325). The X-ray flux before and after passing through the sample was detected by a NaI detector, and the shielding effect of the material was calibrated with a transmittance T=I / I0, where I is the X-ray flux after passing through the sample, and I0 is the initial X-ray flux. The specific test data are shown in Table 1:
[0072] Table 1
[0073] Tube voltage Example 1 Example 2 Example 3 Example 4 50kV 0.0226 0.0208 0.0127 0.0131 100kV 0.0507 0.0486 0.0402 0.0411 150kV 0.1918 0.1864 0.1085 0.1103
[0074] It can be seen from the data in Table 1 that the shielding material (thickness 1.4 mm) prepared by the present invention has a good shielding effect on X-rays. Among them, the samples prepared in Example 3 and Example 4 have a maximum X-ray transmittance of 11.03% under the test condition of a tube voltage of 50-150 kV, and the shielding effect on X-rays is better than that of existing flexible shielding materials.
[0075] The basic performance and mechanical properties of Examples 1 to 4 were tested, and the specific testing methods are as follows:
[0076] Density: Refer to GB / T 4472-2011 Determination of relative density of chemical products;
[0077] Tensile properties: Refer to GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;
[0078] Tear strength: GB / T 529-2008 Determination of tear strength of vulcanized rubber or thermoplastic rubber; the specific test is shown in Table 2:
[0079] Table 2
[0080]
[0081]
[0082] It can be seen from the data in Table 2 that the shielding material prepared by the present invention has higher density and mechanical properties. The density of Example 4 reaches 8.082 g / cm 3 , the tensile strength is 1.71 MPa, the elongation at break is 46%, the tear strength is 4.43 kN / m, and the mechanical properties are excellent. Combined with the data in Table 1, Example 4 also has good X-ray shielding ability.
[0083] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A production process for an X-ray shielding material, characterized in that: The steps include: Step S1: subjecting the nano-silicon carbide whiskers and the nano-carbon tubes to coupling treatment and then evaporating to dryness; Step S2: dry-mixing the shielding powder material, the nano-silicon carbide whiskers processed in step S1, and the nano-carbon tubes for 72 hours to obtain a composite powder material; Step S3: adding liquid silica gel into a stirring kettle, adding composite powder material and mixing evenly under stirring, then adding curing agent and continuing to mix to obtain a composite adhesive material; Step S4: adding the composite adhesive material into a casting machine and extruding it into a casting film, and passing hot air at 40° C. to dry it during the casting process to obtain a semi-solidified film; Step S5: sequentially subjecting the semi-solidified film to infrared irradiation, rolling and ultraviolet irradiation to obtain an X-ray shielding material; The proportions of the raw materials by weight are: shielding powder 86-95%, liquid silicone 4.7-13.8%, nano silicon carbide whiskers 0.1-5%, nano carbon tubes 0.05-4% and curing agent 0.05-0.1%.
2. The production process of an X-ray shielding material according to claim 1, characterized in that: The shielding powder material includes tungsten powder, molybdenum powder, titanium powder and rhenium powder, and the mass ratio of the powders is 1:0.47-0.52:0.1-0.2:0.2-0.3 respectively.
3. The production process of an X-ray shielding material according to claim 2, characterized in that: Tungsten powder is spherical particles, the Fischer-Strauss particle size of tungsten powder is 10-20 μm, the Fischer-Strauss particle size of molybdenum powder is 3-4 μm, the Fischer-Strauss particle size of titanium powder is 1-3 μm, and the Fischer-Strauss particle size of rhenium powder is 3-5 μm.
4. The production process of an X-ray shielding material according to claim 1, characterized in that: The specific method of the coupling treatment is: ultrasonically disperse the nano-silicon carbide whiskers and nano-carbon tubes in an ethanol solution, add KH550 and ultrasonically disperse them again, and then soak them for 24 hours.
5. The production process of an X-ray shielding material according to claim 1, characterized in that: The infrared wavelength of infrared irradiation is 5-30μm, the irradiation power is 220-300W, the irradiation distance is 10-15cm, and the irradiation time is 25-40min.
6. The production process of an X-ray shielding material according to claim 1, characterized in that: The rolling pressure is 6-10kN.
7. The production process of an X-ray shielding material according to claim 1, characterized in that: The ultraviolet wavelength of ultraviolet radiation is 100-200nm, the irradiation power is 150-200W, the irradiation distance is 10-20cm, and the irradiation time is 20-30min.
8. An X-ray shielding material, characterized in that: Made by the production process described in any one of claims 1 to 7.
Citation Information
Patent Citations
Coated carbon fiber reinforced ABS / PP electromagnetic shielding composite material and preparation method thereof
CN107746505A
Magnetic ultra-soft X / gamma ray protective diaphragm material with decorative or directly printable function and preparation method of magnetic ultra-soft X / gamma ray protective diaphragm material
CN109887630A